ANALISIS PENERAPAN SAK EMKM ATAS PERSEDIAAN PADA CV. JAYA MAKMUR - Halim, Evelyna Muliadi; Tinangon, Jantje; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
In a merchandising company, inventory is a significant asset, and becoming a more important resource than an asset.Â  The application of inventory carried out by CV. Jaya Makmur is still not in accordance with SAK EMKM, which is not journalizing the inventory of merchandise. This study aims to determine the recognition & measurement and presentation of merchandise inventory on CV. Jaya Makmur. This research is a type of descriptive qualitative research. The research method used is descriptive method, which describes the research results according to the facts found in the field. The results obtained indicate that the application of SAK EMKM on CV. Jaya Makmur is still not suitable. In recognizing its inventories, the entity recognizes inventories at the value of the purchase transaction, and does not add transportation costs for purchases, returns purchases, and purchase discounts, while in measuring its inventory the entity does not measure inventory based on standard or retail method, and in its presentation does not record/ journalize inventory merchandise.